Empagliflozin Induces White Adipocyte Browning and Modulates Mitochondrial Dynamics in KK Cg-Ay/J Mice and Mouse Adipocytes - Xu, Linxin; Xu, Chaofei; Liu, Xiangyang; Li, Xiaoyu; Li, Ting; Yu, Xiaochen; Xue, Mei; Yang, Jing; Kosmas, Constantine E.; Moris, Dimitrios; Sanchis-Gomar, Fabian; Yoshida, Naofumi; et al. (Frontiers in Physiology, 2021)
Background: White adipose tissue (WAT) browning is a promising target for obesity prevention and treatment. Empagliflozin has emerged as an agent with weight-loss potential in clinical and in vivo studies, but the mechanisms underlying its effect are not fully understood. Here, we investigated whether empagliflozin could induce WAT browning and mitochondrial alterations in KK Cg-Ay/J (KKAy) mice, and explored the mechanisms of its effects. Methods: Eight-week-old male KKAy mice were administered empagliflozin or saline for 8 weeks and compared with control C57BL/6J mice. Mature 3T3-L1 adipocytes were treated in the presence or absence of empagliflozin. Mitochondrial biosynthesis, dynamics, and function were evaluated by gene expression analyses, fluorescence microscopy, and enzymatic assays. The roles of adenosine monophosphate–activated protein kinase (AMPK) and peroxisome proliferator–activated receptor-γ coactivator-1-alpha (PGC-1α) were determined through AICAR (5-Aminoimidazole-4-carboxamide1-β-D-ribofuranoside)/Compound C and RNA interference, respectively. Results: Empagliflozin substantially reduced the bodyweight of KKAy mice. Mice treated with empagliflozin exhibited elevated cold-induced thermogenesis and higher expression levels of uncoupling protein 1 (UCP1) and other brown adipose tissue signature proteins in epididymal and perirenal WAT, which was an indication of browning in these WAT depots. At the same time, empagliflozin enhanced fusion protein mitofusin 2 (MFN2) expression, while decreasing the levels of the fission marker phosphorylated dynamin-related protein 1 (Ser616) (p-DRP1(Ser616)) in epididymal and perirenal WAT. Empagliflozin also increased mitochondrial biogenesis and fusion, improved mitochondrial integrity and function, and promoted browning of 3T3-L1 adipocytes. Further, we found that AMPK signaling activity played an indispensable role in empagliflozin-induced browning and mitochondrial biogenesis, and that PGC-1α was required for empagliflozin-induced fusion. Conclusion: Our results suggest that empagliflozin is a promising anti-obesity treatment, which can immediately induce WAT browning mitochondrial biogenesis, and regulate mitochondrial dynamics.